Mental Health Comorbidity In HIV-positive Zambian Adults Who Consume Alcohol. (30th September 2020) - Kanguya, T; Vinkoor, M; Sharma, A; van Wyk, S; Paul, R; Mayeya, J; Murray, L K; Sikazwe, I; Kane, J C
Abstract: Background: Alcohol abuse is common in Zambia and a growing threat to achieving the 90 90 90 treatment target to ending the HIV epidemic. Brief counselling is offered but has limited effectiveness possibly because it does not address the mental health issues that underpin drinking behavior. We assessed the frequency and nature of comorbid mental health issues in HIV-positive drinkers in Zambia. Methods: As part of an ongoing randomized control trial (NCT03966885), we recruited HIV positive adults on ART who reported at least 1 alcoholic drink in the previous 3 months from two clinics in Lusaka, Zambia. Using audio computer assisted self-interviewers, we captured demographic information and screened for unhealthy alcohol use (AUDIT), depression (CES-D), trauma (HTQ) and other substance abuse (ASSIST). These instruments have previously been validated in Zambia. Established cut-offs were used to define unhealthy alcohol use (AU), depression (DEP), post-traumatic stress disorder (PTSD) and substance abuse (SU). Results: Among 300 individuals reporting any alcohol use, 165 agreed to screening. 155 participants were recruited, including 93 men and 62 women. Nearly all screened 146 (94.2%) had unhealthy alcohol use and 9 (5.8%) had low to moderate alcohol scores. Comorbid mental health issues were present in 72 % of unhealthy drinkers, most commonly depression 46 (31.5 %) and trauma 35 (24 %). Non-alcohol substance use (7.6 %) comorbidities where less prevalent than mental health comorbidities among those with unhealthy alcohol use. Conclusions: Among urban Zambian adults living with HIV who reported alcohol consumption at their ART clinic, unhealthy use was the norm; moderate alcohol use was rare. Comorbid mental health issues (particularly depression and trauma) are highly prevalent among unhealthy drinkers with HIV. These data suggest that all unhealthy drinkers should be screened for mental health issues. Key messages: Alcohol Abuse In HIV Patients Is Common In Zambia. HIV Patients Abusing Alcohol Suffer From Depression and Trauma.